An Examining the Firm Life-Cycle Theory of Dividends in Indonesia - Murtiana, Suci; Yulianto, Arief (Management Analysis Journal, 2018)
This study aims to examine the company’s propensity of manufacture companies to pay dividend effected by retained earning to total equity (RE/TE) in their life cycle stages by controlling profitability, sales growth and firm size. Furthermore, this study also explains the company’s propensity to pay a dividend before and after the global crisis particularly Subprime Mortgage. The firm ’s life cycle consists of four stages: start-up, growth, mature and decline stage. This research is explanatory research by using regression qualitative response analysis. The purposive sampling used to determine the research sample. Thus 75 manufacture companies which are listed on the Indonesia Stock Exchange (IDX) in 2005 to 2016 have been selected as the research sample. This result shows that the Manufacture companies listed on IDX in 2005 to 2016 tend to pay a dividend on the mature stage before and after Subprime Mortgage. In the mature stage, the manufacture companies have a bigger probability of paying a dividend rather than in start-up, growth and decline stage in 2005 to 2016. The company’s propensity to pay a dividend in the mature stage is bigger than the start-up, growth and decline stage before and after the Subprime Mortgage crisis. The conclusion of this study explains that the manufacture companies employ the life-cycle theory of dividend in their dividend policy.